Hubungan Pengetahuan Kesehatan Reproduksi dengan Perilaku Seksual Remaja - Divya Salsabilla Vemala Putri; Andriyani Andriyani; Nurmala Lusida (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Adolescence is a transition from childhood to adulthood that experiences development of access to enter the adult phase including the function of reproduvtive organs. Deviant sexual behavior usually occurs among adolescents who have less knowledge of reproductive health and up finding out through peers or the internet whose truth is not yet know. Lack of information in this aspect encourges sexual behavior, which leads to unwanted pregnancies and sexually transmitted diseases, as well as mental disorders. The purpose of this study was to determine the relationship between reproductive health knowledge and adolescent sexual behavior. The method used is a quantitative or cross-sectional approach, involving several respondents who were selected purposively. The research instrument was  a standardized questionnaire that passed the validity and reability test. The results showed a relationship between the level of reproductive health knowledge and sexual behavior in adolescents, where adolescents who have broader insights show good or responsible sexual behavior. From the research result, it is concluded that there is a need for a comprehensive reproductive health education program for adolscents in schools, families, and social environments to build safe sexual behavior.